Improved field emission from appropriately packed TiO2 nanorods: Designing the miniaturization. (February 2019) - Pathak, Devesh K.; Chaudhary, Anjali; Mishra, Suryakant; Yogi, Priyanka; Sagdeo, P.R.; Kumar, Rajesh
Abstract: An improved electron field emission (FE) property from vertically aligned TiO2 nanorods (TNR) on conducting fluorine doped tin oxide coated glass substrate, prepared by hydrothermal technique, has been reported here. The TNRs having high aspect ratio with appropriate separation were prepared by optimizing the nucleation temperature. The TNR density has been optimized to cease the screening effect in closely packed nanorods. The well aligned rods have been designed so that the applied field is equally distributes on each rod to improve the electron emission. The morphology of the nanorod has been studied using scanning electron microscopy and observed FE current density-field response has been analysed within the frame work of Fowler-Nordheim modelling. Two orders of magnitude enhancement in the electric field has been observed for this kind of geometry giving improved turn on field and field enhancement factor of 0.2 V/μm and 37 thousands respectively. Graphical abstract: Image 1 Highlights: To addresses the shortcomings of previously reported field emission from Titania nanostructures. Well-aligned Titania nanorods feel the same electric field under bias so that a low threshold field can be achieved. The Titania nanorods are appropriate distance apart to avoid screening effect for improved field emission. A very high field enhancement factor of 37 thousand has been reported from titania nanorods. A low turn-on and threshold fields has been observed which is very good for applications like displays.